Possibility of Using Mulberry Paper Products for Food Packaging - BANDAVONG, Viraxay (Souphanouvong University Journal Multidisciplinary Research and Development, 2025)
The aim of present was to study the possibility of using mulberry paper products for food packaging. Three steps were conducted such as surveyed paper package shop(mulberry paper handmade products and mulberry paper imported), package products from 3 types (rigid box, RB), (triangle pack, TP), (square box, SB) and 9 sizes as RB1,2,3; TP4,5,6; SB7,8,9 and consumer test food packaging evaluation were regarding the products’ characteristics such as overall acceptance, sizes, beauty model, texture, strengths, thickness, and easy-to-use. All data collected were statistical analysis. Results of surveying for householder factory production of mulberry paper had box, envelop, square box about 20% internal production and the mulberry paper most imported from Thailand, China and Vietnam 80%. Then 3 types see also three dimensions as width, length, depth (25 x 25 x 6cm) RB, (21 x 15 x 12cm) TP and (25 x 15 x 10cm) SB, respectively. The mulberry paper products were any different dimension. Consumer test for the packaging products were showed the acceptance score range from moderate (6.74 – 7.29), high (6.64 – 7.07) and very higher (7.56 – 8.29) from RB2, TP3 and SB3 acceptance sizes easy-to-use, beauty model, and overall (7.29, 7.07 and 8.29), respectively. Overall results showed that paper products for food package most imported so pulp mold, packaging quantity, packaging type of paper different arrange imported and exported. Consumers associate paper packaging with novelty, uniqueness, premium Ness, exclusivity, and high quality. Retailers as well perceive paper packaging as unique and premium; however, have paper as a packaging material is generally regarded as a more environmentally sustainable than plastic. A barrier layer is required to ensure food quality preservation, and survival of the product throughout the entire supply chain. This can be suggestion that handmade and package industry different so can be used as potential materials develop mulberry paper products in the future.